The betaine/GABA transporter and betaine: roles in brain, kidney, and liver - Kempson, Stephen A.; Zhou, Yun; Danbolt, Niels C. (Frontiers in Physiology, 2014)
The physiological roles of the betaine/GABA transporter (BGT1; slc6a12) are still being debated. BGT1 is a member of the solute carrier family 6 (the neurotransmitter, sodium symporter transporter family) and mediates cellular uptake of betaine and GABA in a sodium- and chloride- dependent process. Most of the studies of BGT1 concern its function and regulation in the kidney medulla where its role is best understood. The conditions here are hostile due to hyperosmolarity and significant concentrations of NH4Cl and urea. To withstand the hyperosmolarity, cells trigger osmotic adaptation, involving concentration of a transcriptional factor TonEBP/NFAT5 in the nucleus, and accumulate betaine and other osmolytes. Data from renal cells in culture, primarily MDCK, revealed that transcriptional regulation of BGT1 by TonEBP/NFAT5 is relatively slow. To allow more acute control of the abundance of BGT1 protein in the plasma membrane, there is also post-translation regulation of BGT1 protein trafficking which is dependent on intracellular calcium and ATP. Further, betaine may be important in liver metabolism as a methyl donor. In fact, in the mouse the liver is the organ with the highest content of BGT1. Hepatocytes express high levels of both BGT1 and the only enzyme that can metabolize betaine, namely betaine:homocysteine –S-methyltransferase (BHMT1). The BHMT1 enzyme removes a methyl group from betaine and transfers it to homocysteine, a potential risk factor for cardiovascular disease. Finally, BGT1 has been proposed to play a role in controlling brain excitability and thereby represents a target for anticonvulsive drug development. The latter hypothesis is controversial due to very low expression levels of BGT1 relative to other GABA transporters in brain, and also the primary location of BGT1 at the surface of the brain in the leptomeninges. These issues are discussed in detail.